Teknik Yoga Sebagai Intervensi dalam Melakukan Anger Management pada Wanita Dewasa Awal - Anissa Lestari Kadiyono; Febbyros Anmarlina (Universitas Islam Indonesia, 2016)
The purpose of this study is to examine the effect of yoga technique to improve anger management. The design of this study is a quasi-experimental method. The study compared two groups: group with yoga (n= 60) and no yoga (n = 60). Respondents aged between 20-40 years (M = 46.15, SD = 7.017). Data processing was performed with the Mann-Whitney U test on two groups of test criteria reject H0 if the pvalue <0.05. The results showed a p-value of 0.000, which means there was a difference anger management in women with yoga than those women without yoga. This research showed that yoga techniques becomes alternative way to manage angry emotions. Yoga helped anger management,calmminds, reduce stress, provide improved awareness and alertness of the body.Keyword : anger management, young adult, yoga techniques